Beyond the crash : overcoming the first crisis of globalization - Brown, Gordon, 1951- (New York : Free Press, 2010)
Former British Prime Minister and Chancellor of the Exchequer Gordon Brown believes the international financial crisis can be reversed, but that the world's leaders must work together if we are to avoid a decade of lost jobs and low growth. Brown speaks both as someone who was in the room driving discussions that led to some crucial decisions, and as an expert renowned for his financial acumen. No one who had Brown's access has written about the crisis yet, and no one has written so convincingly about what the global community must do next in order to climb out of this abyss. As he sees it, the crisis was brought on not simply by technical failings, but by ethical failings too. He argues that markets need morals, and suggests that the only way to truly ensure that the world economy does not flounder again is to institute a banking constitution and a global growth plan.--From publisher description.
"All I need is overnight finance" -- The problem foreseen: lessons from the Asian crisis -- The problem revealed: capitalism without capital -- The problem assailed: the one-trillion-dollar plan -- Going for global growth and jobs -- The American challenge -- China's opportunity -- India and the Asian economies -- Living with the euro -- Post-crisis Africa -- A plan for global growth.
Includes bibliographical references (p. 285-292) and index.
Keywords: Global Financial Crisis, 2008-2009.; Financial crises; International trade; International finance; International economic relations; Economic policy -- International cooperation; Economic development -- International cooperation